From participation to power: Advancing women’s leadership in rural development - Kosec, Katrina (International Food Policy Research Institute, 2025)
The International Day of Rural Women (October 15) highlights the essential roles that rural women play in sustaining households, managing natural resources, and contributing to rural economies. Yet even as they participate extensively in agriculture and local organizations, women’s ability to influence the policies and institutions that shape their lives often remains limited.